Notch and Aryl Hydrocarbon Receptor Signaling Impact Definitive Hematopoiesis from Human Pluripotent Stem Cells. (1st April 2018) - Leung, Amy; Zulick, Elizabeth; Skvir, Nicholas; Vanuytsel, Kim; Morrison, Tasha A.; Naing, Zaw Htut; Wang, Zhongyan; Dai, Yan; Chui, David H. K.; Steinberg, Martin H.; Sherr, David H.; Murphy, George J.
Abstract : Induced pluripotent stem cells (iPSCs) stand to revolutionize the way we study human development, model disease, and eventually, treat patients. However, these cell sources produce progeny that retain embryonic and/or fetal characteristics. The failure to mature to definitive, adult-type cells is a major barrier for iPSC-based disease modeling and drug discovery. To directly address these concerns, we have developed a chemically defined, serum and feeder-free–directed differentiation platform to generate hematopoietic stem-progenitor cells (HSPCs) and resultant adult-type progeny from iPSCs. This system allows for strict control of signaling pathways over time through growth factor and/or small molecule modulation. Through direct comparison with our previously described protocol for the production of primitive wave hematopoietic cells, we demonstrate that induced HSPCs are enhanced for erythroid and myeloid colony forming potential, and strikingly, resultant erythroid-lineage cells display enhanced expression of adult β globin indicating definitive pathway patterning. Using this system, we demonstrate the stage-specific roles of two key signaling pathways, Notch and the aryl hydrocarbon receptor (AHR), in the derivation of definitive hematopoietic cells. We illustrate the stage-specific necessity of Notch signaling in the emergence of hematopoietic progenitors and downstream definitive, adult-type erythroblasts. We also show that genetic or small molecule inhibition of the AHR results in the increased production of CD34 + CD45 + HSPCs while conversely, activation of the same receptor results in a block of hematopoietic cell emergence. Results presented here should have broad implications for hematopoietic stem cell transplantation and future clinical translation of iPSC-derived blood cells. Abstract : A chemically defined platform for the generation of hematopoietic stem-progenitor cells and resultant adult-type blood cells from human induced pluripotent stem cells via the stage-specific modulation of the Notch and aryl hydrocarbon receptor pathways.